The Influence of Taste, Price, Store Atmosphere, and Service Quality on Consumer Satisfaction at Warkop Gb 2 - Yusuf, M; Zalikha*, Zalikha; Ariska, Emalia; Mulyadi, Mulyadi (Universitas Syiah Kuala, 2024)
This research aims to determine the influence of taste, price, store atmosphere and service quality on consumer satisfaction. This type of research is associative research. Data collection in this research was carried out through a survey approach with a quantitative descriptive research type by distributing questionnaires to 100 respondents, while the population used in this research was customers of GB 2 Bireuen warkop. Data collection techniques were carried out using interviews, questionnaires and documentation studies. The data analysis tool used in this research uses SPSS. The data analysis technique in this research is descriptive analysis. The results of this research show that taste, price, store atmosphere and service quality influence customer satisfaction at warkop GB 2 Bireuen